A 6-week Sprint Interval Training Program Changes Anaerobic Power, Quadriceps Moment, and Subcutaneous Tissue Thickness - Han, Seunguk; Lee, Hyungkyu; Kim, Hyungkee; Kim, Dasol; Choi, Changkyu; Park, Jihong (International Journal of Sports Medicine, 2017)
We examined the effects of a 6-week 40-m one-way sprint interval training program (based on sprint time). 13 untrained healthy male collegiate students performed six 40-m sprints with a 60-s resting interval between sprints during the first week, and one sprint was added each week until the sixth week. If the 40-m sprint time exceeded 110% of the fastest baseline 40-m sprint time, the run was repeated. Repeated-sprint cycling test (every 3 weeks), quadriceps moment (every 2 weeks), and abdominal and thigh subcutaneous tissue thickness (every 2 weeks) were measured. Compared to baseline, mean power output improved at week 3 (16.27 vs. 17.73 Watt/kg, p=0.004). Regardless of side, quadriceps moment began to increase at week 4 (2.88 vs. 3.15 N·m/kg, p=0.03). Subcutaneous tissue thickness was reduced at week 2 (abdominal: 11.19 vs. 9.65 mm, p=0.01; thigh: 9.17 vs. 8.12 mm, p=0.009). Our results suggest that (1) sprint training with an intensity of 110% of the fastest baseline 40-m sprint time with the addition of one sprint per week produces similar effects to other training programs, and (2) untrained individuals need 4 weeks of training for strength development in the quadriceps and 2 weeks for reduction in fat tissue thickness.
Keywords: 40-m sprint; repeated-sprint cycling test; knee extension torque; adipose tissue; heart rate